Aggregation-induced phosphorescence of an anthraquinone based emitter - Goudappagouda; Nidhankar, Aakash D.; Nayak, Rashmi A.; Babu, Sukumaran Santhosh (Organic & Biomolecular Chemistry, 2021)
Room temperature phosphorescence (RTP) of metal-free organic molecules is a hot topic of current research interest. RTP can be enhanced through aggregation, crystallization, and the support of polymers and host-guest assemblies. The characteristics of highly phosphorescent aggregates formed from conventional chromophores make them ideal candidates for many potential applications. In this direction, we focused on the aggregation-induced phosphorescence of an anthraquinone derivative AqC6 in solution and in crystal state. The weakly emissive dilute solution exhibits a tunable emission with enhanced intensity and room temperature phosphorescence by increasing the concentration and solvent-antisolvent combination. The enhanced phosphorescence of crystals has been recreated in the solution by making use of aggregation. Interestingly, the support of PMMA enabled AqC6 to achieve enhanced processability, phosphorescence lifetime (174 ms) and quantum yield (5%).